LAYANAN BIMBINGAN PARENTING MELALUI KEGIATAN HOME VISIT DI SDIT AL-HIDAYAH SUMENEP - Mafruhah; Mas’odi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The parenting style provided by parents greatly influences a child's development, both physically and psychologically. This service aims to broaden parents' understanding of parenting practices at home. The purpose of the parenting service program through home visits is to educate parents or guardians about proper parenting practices that are aligned with the child’s developmental stage. When children are treated with an appropriate parenting style, it can stimulate their growth and development. This study uses a qualitative approach with a case study method. The results show that parenting guidance services can educate parents on how to raise school-aged children, enhance their understanding of the importance of parenting styles, support character development in children, and help build children's self-confidence.